Cutting out the camel-like knees of St. James: the de viris illustribus tradition in the twelfth-century renaissance. Issue 264 (5th April 2021) - Byrne, Philippa
Abstract: This article examines the revival of the de viris illustribus genre in the twelfth century. These catalogues of the most important Christian authors were modelled on a template created in late antiquity by Jerome, but adopted new attitudes to what constitutes distinguished Christian literary activity. They regard the editing, collecting, and re-ordering of texts as equal to the composition of new works, and recognize legal codification as a noteworthy activity. As such, they represent the broadening out of a Latin Christian literary canon. These texts complicate our ideas about the relationship between 'authority' and 'amplification' in the twelfth-century renaissance.